Serial monitoring of the audiogram in hearing conservation using Gaussian processes - McMillan, Garnett P.; DeBacker, J. Riley; Hungerford, Michelle; Konrad-Martin, Dawn (Frontiers in Audiology and Otology, 2024)
Most hearing conservation programs repeatedly monitor a subject's pure tone thresholds before, during, and after exposure to audiopathic agents. Changes to the audiogram that meet significant shift criteria such as ASHA, CTCAE, and so forth are considered evidence of audiopathic injury. Despite a wide variety of definitions for significant change, all current serial monitoring methods are biased due to regression to the mean and are prone to inconclusive results. These problems diminish the diagnostic accuracy and utility of serial monitoring. Here we propose adopting Gaussian processes to address these issues in a manner that maximizes time efficiency and can be administered using portable equipment at the point of care.